Design Of fish feeder control system and water pH monitoring in Tilapia Pond based on Internet of Things (IoT) using Mini PC - Ardini, M. Syahzali; Muskhir, mukhlidi; Habibullah; Ranuharja, Fadhli (Journal of Industrial Automation and Electrical Engineering, 2024)
The aquaculture sector currently has a real contribution to foodsecurity, including increased production, animal protein consumption,employment, income and regional development. Some problems intilapia farming are manual feeding and unstable water pH levels. Thisresearch aims to design and build an automatic control system for fishfeeders and monitoring water pH in tilapia ponds based on the Internetof Things (IoT). This system uses a Raspberry Pi as the systemcontrol. In the feeding mechanism, the HX711 load cell sensor is usedto weigh the feed, the servo motor functions as the opening and closingof the main feed container, and the DC fan acts as a blower of theweighed feed into the pond area. In addition, a PH-4502C sensor isused to measure the acidity (pH) of the pond water in real-time. Alldata related to feed weight and water pH are displayed through a webserver interface that can be accessed remotely by users. This system isexpected to improve the efficiency of feeding and monitoring waterquality, thus supporting optimal tilapia growth. The test results showthat this system is able to operate well and provide accuratemonitoring results as well as timely feed control and in accordancewith the needs of tilapia.